The powerless starchitect: How Zaha Hadid became the first person working on the Al-Wakrah stadium that actually did die - van der Hoeven, Frank (project baikal, 2016)
Starchitect Zaha Hadid won the bid to design one of the planned stadiums for the 2022 FIFA World Cup event in Qatar. Her design for the Al-Wakrah stadium became the centrepiece of a discussion on the role that starchitects play in society. That debate reached a boiling point in August 2014, and resulted in a digital lynching party that sheds serious doubts on the ethics and professionalism of architectural critics and journalists alike.
Keywords: starchitect; Zaha Hadid; Al-Wakrah stadium; 2022 FIFA World Cup; Qatar; migrant workers; Nepal; India; deaths; architectural critics; Martin Filler; The Guardian